Cry blood, Apache - Starrett, Jack, 1936-1989; McCrea, Jody, 1934-2009; Liberty Entertainment Inc.; Cinetel Films ([Los Angeles, CA] : Liberty Entertainment Inc., 1970)
A party of five men discover gold in a small Apache camp. They murder everyone there except for one young woman, who they keep alive hoping she'll lead them to more gold. Only Pitcalin among the five men shows kindness to the prisoner. An Apache brave who was away from the camp discovers the massacre and buries the dead. Then he tracks the murderers and brings slow but steady vengeance upon them. --
Jody McCrea, Marie Gahua, Dan Kemp, Robert Tessier, Jack Starrett, Don Henley, Ric Nervik, Joel McCrea, Marcos Rudnick.
Director of photography, Bruce Scott; editor, T. Robinson; music, Elliot Kaplan.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 7, 2015)
Keywords: Western films; Feature films; Internet videos; Streaming video